(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Dental anatomy is an important part of dentistry and medicine and is important for the health and general well-being of the human body. Teeth play an important role not only in digestion, but also in speech, facial expressions and overall aesthetics. Therefore, the process of teaching dental anatomy is very important for students and practicing dentists. Modern pedagogical technologies play an important role in improving the quality of teaching and improving the level of students’ learning in this process.